A comparative nasal anthropometric measurement in unilateral cleft lip and palate patients after rhinoplasty and normal population - Stephen Kalong, Daphne Dewi Anak (2015)

(untitled)
The nasal deformity in cleft has been viewed as the most challenging reconstructive problems in cleft surgery. Nose anthropometric measurement in post cleft repair patient is to determine the goal of surgical repair in producing nose in most “normal” outcome.Nose anthropometric measurement in these patients is to determine that this goal is achieve by comparing measurements in post rhinoplasty with cleft nasal deformity with normal population.A retrospective study was carried out in Department of Plastic and Reconstructive Surgery, Hospital Kuala Lumpur. Direct anthropometric measurements were performed on post rhinoplasty patient with cleft nasal deformity and results were compared with normal population. A total of 72 patients were participated in this study. All open rhinoplasty were performed with augmentation with rib cartilage graft. Eight anthropometric measurements selected included nasal height (n-sn), nasal width (al-al), nasal tip protrusion (sn-prn), columella length (sn-c’), width of columella (sn’-sn’), width between the facial insertion (ac-ac) and width of nostril floor of right and left (sbal-sn). The post rhinoplasty patients had an increase in nasal height, nasal tip protrusion and columella height. The nasal index in both group are within mesorrhine nose type, the UCLP group had higher nasal index compared with control group. Open rhinoplasty with rib cartilage graft had improving esthetic appearance of nose in cleft nose deformity. Further additional other surgical techniques may enhance further the appearance by addressing other issues in secondary cleft nose deformities.